The Effect of Current Ratio, Net Profit Margin, Return on Assets and Return on Investment on Share Price in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2018-2021 Period - Ronald Hasudungan Rajagukguk; Oidarmawati Halawa; Febry Sinta Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the effect of the current ratio, net profit margin, return on assets, and return on investment on stock prices in manufacturing companies in the food sub-sector and Beverages Registered on the Indonesia Stock Exchange (IDX) for 2018 – 2021. The data used is sourced from financial data on the Indonesia Stock Exchange via the website www.idx.co.id, and a selection has been made based on predetermined criteria. The population used in this study were food and beverage companies, a total of 28 companies, using a purposive sample, the samples obtained were 19 companies. With this research it is hoped that it can become a science to help further researchers as well as students or the general public who need a source of information. From the research it can be seen that the Current Ratio, Net Profit Margin, Return on Assets, and Return on Investment have a simultaneous (together) effect on the Stock Price. Variable Current Ratio (Current Ratio), Net Profit Margin (Net Profit Margin) and Return On Assets (Return On Assets) have a partial and significant effect on stock prices, while the variables Return On Investment (Return On Investment) have no effect and are partially significant on the share of prices in food and beverage companies listed on the Indonesia Stock Exchange for the period 2018 – 2021.